The Angus Saga: How do fluidization of knowledge, hypermedia translation and defiction combine for a fictional world of the MacLachlan Clan? - Arrizabalaga, Maria Ines (2021)
O primeiro guerreiro, the initial volume of Orlando Pães Filho´s A saga de Angus (The Angus Saga), was published in Brazil in 2003, appearing in different products of new media ever since. I plan to use three pairs of concepts to understand O primero guerreiro: the fluidization of knowledge and hypermedia translation for explaining the convergence of Literature and the Internet; defictionalization and quasi-Literature both in the passage of Literature to virtual environments, and in the saga´s reference to historical archives; post-translation applied to new media products responding to the determinations of creative economy, and the ecosystem mode in which functional actives of culture interrelate. I attempt to shed light on: i) the multi talent requirements implied in a literary fact translated to the new media and into English for the explicit purpose of expanding the consuming audience and consequently the scope of literary critics and translation scholars; ii) digital nomadism as characterises Pães Filho, his readers, literary critics and translation scholars, all of them dealing with products in transit from History to Literature, and English-dominated virtual environments; iii) the dynamics of literary memory effects in the framework of Literature, Media and Translation Studies.